Pemetaan Penyakit Pneumonia di Provinsi Jawa Timur - Sulis Susanti (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
Morbidity and mortality in infants can be caused by various reasons one of which is pneumonia. UNICEF reported that 21,000 children under fi ve in Indonesia died due to pneumonia in 2012. East Java one of the provinces with the high level of infant pneumonia. Recording and reporting the results of the year 2012 the number of suff erers reported by Regency/City is 84.392 people. The purpose of this study was to describe how the distribution and causes of pneumonia cases in the province of East Java using geoda program. The sample used in this study is the total of the population that is 38 district/city in East Java province. The variables studied were immunized against measles, vitamin A, a clean and healthy life behavior (PHBS), poor nutrition. The results of this study show that the coverage of measles immunization lowest in 5 districts and 4 cities, vitamin A is lowest in 8 districts and 1 city, 1 PHBS lowest in the city and 7 districts, malnutrition was highest in 7 districts and 4 Cities. In accordance with the results of the study are expected counseling about the cause of pneumonia can be scaled according to the conditions of the region, especially the parents.